PENERAPAN JOB SHEET PADA PEMBELAJARAN MENGGAMBAR BAGIAN DAN BENTUK BUSANA SISWA KELAS X KOMPETENSI TATA BUSANA MA PLUS KETERAMPILAN MAN 3 KEDIRI - Pradani, Nikenia Vindy; Yuniati, Mita; Rahayu, Imami Arum Tri; Arifiana, Deny (Jurnal Socia Akademika, 2023)
The background of this research is the lack of attention of students during learning, the learning process uses lecture and demonstration methods. Limited supporting tools for material for drawing parts and shapes of clothing, resulting in the need for teaching materials that aim to help students in drawing parts and shapes of clothing which can also be done independently. Students tend to be bored and less motivated to explore the material. The purpose of this research is to determine the implementation of the job sheet in learning to draw clothing parts and shapes, students' responses to the application of the job sheet on the results of learning to draw clothing parts and shapes, student learning outcomes after applying the job sheet to learning to draw clothing parts and shapes. This type of research uses pre-experiments with a One Shoot Case Study pattern. The results of applying the job sheet to the material on drawing parts and shapes of clothing produced an average percentage of student behavior of 80.2% and an average percentage of teacher behavior of 92%. The results of student responses produced very good responses with an average percentage of 85.7%. Student learning outcomes have an average percentage of 97.2% which have met the minimum requirements for learning completeness. The findings of this research are able to help students understand the material so that they achieve completeness with a score beyond the Criteria for Achieving Learning Objectives.